Analisis Dampak Pariwisata Berkelanjutan terhadap Kinerja Keuangan Destinasi Wisata: Perspektif Sustainable Development Goals (SDGs) - Wiwit Pawitri; Muhammad Syahrudin; Laras Angelia Nirwana Sari; Liya Setiawati (LPPM UBP, 2026)
Research on sustainable tourism has grown significantly in recent years as increasing attention is given to sustainability issues within the tourism sector. However, empirical studies that specifically examine the impact of sustainable tourism on destination financial performance within the framework of the Sustainable Development Goals (SDGs) remain relatively limited. Therefore, this study aims to analyze the relationship between sustainable tourism, the SDGs, and destination financial performance. This study employs a quantitative research approach using a survey method involving tourism stakeholders in West Java Province, Indonesia. Data were collected through structured questionnaires measured using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. A total of 200 respondents were selected using purposive sampling. The study is grounded in Stakeholder Theory and the Resource-Based View (RBV) to explain the relationship between sustainable tourism practices and the economic performance of tourism destinations. The results indicate that sustainable tourism has a positive and significant effect on destination financial performance. In addition, the SDGs also have a positive and significant effect on destination financial performance. However, the moderating effect of SDGs on the relationship between sustainable tourism and destination financial performance is not statistically significant. This study contributes to the sustainable tourism literature by integrating the SDGs framework as a moderating variable in examining the economic implications of sustainable tourism practices on destination financial performance.